Effects of tourism on seasonal movements and fine-scale habitat selection of African lions and spotted hyenas in Etosha National Park, Namibia - Jessica R. Patterson; Stéphanie Périquet-Pearce; Madeline H. Melton; Brennan PetersonWood; Dipanjan Naha; Claudine Cloete; James C. Beasley (Global Ecology and Conservation)
Understanding the drivers of habitat selection for apex predators, such as African lions (Panthera leo) and spotted hyenas (Crocuta crocuta), is a vital component of conservation efforts. Large carnivores are especially vulnerable to anthropogenic pressures, which are increasing in areas of Sub-Saharan Africa. As wildlife-based tourism increases human-wildlife interactions, it is crucial to better understand predator habitat selection to inform conservation strategies. In this study, we used GPS collar data from 14 lions and nine hyenas tracked between 2016 and 2024 in Etosha National Park, Namibia to develop step selection functions to determine how roads, waterholes, and vegetation influenced habitat selection during periods of high and low tourism. Our results show that within a protected area popular for tourism, lion and hyena habitat selection is influenced by environmental and anthropogenic factors during both day and night. However, the distribution and availability of habitat and vegetation was a more important driver of habitat selection than anthropogenic factors in our study system. In particular, during both seasons water availability was a main driver of habitat selection for lions. Lions and hyenas selected for areas near roads with less tourism activity, which may indicate they avoid certain areas to minimize interactions with humans. Vegetation density influenced selection by both species, with lions selecting for areas with low vegetation density and hyenas selected for areas with high vegetation density in both seasons. These results contribute to our understanding of lion and hyena habitat selection as human activities continue to increase across the globe.